Psychological Well-Being Warga Binaan Lapas Wanita Kelas IIA Sukamiskin Bandung Menjelang Pembebasan - Karima, Dhuhita; Siswadi, Ahmad Gimmy Prathama; Abidin, Zainal (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2019)
AbstractA good level psychological well-being is important for inmates’ prerelease to have a good function in their new surroundings and as a predictor of resilience. Women inmates who will be release can have psychologicall distress that have negative consequences to their level of psychological well-being. The aim of this research is to see psychological well-being in inmates’ during their prerelease. This is a descriptive and quantitative research using 42-item Ryff Psychological Well-Being Scale. The respondents were 33 inmates’ during their prerelease time in Lembaga Pemasyarakatan Wanita Klas IIA Sukamiskin Bandung (Women Prison in Sukamiskin Bandung) and were taken using accidental sampling in non-random sampling method. The data then were analyzed by using distribution of frequency in the percentations. The level of psychological well-being was divided into three categories: high, middle, and low psychological well-being, and the result of this research shows that most of the inmates’ have moderate level of psychological well-being. High scores were mostly found in positive relation to others dimension and low scores were mostly found in self-acceptance dimension.Keyword: prerelease, psychological well-being, inmates AbstrakPsychological well-being yang baik diperlukan warga binaan menjelang pembebasan agar dapat memaksimalkan potensi untuk beradaptasi di lingkungan masyarakat dan sebagai prediktor tingkat resiliensi. Berdasarkan fenomena yang terjadi, sebagian warga binaan wanita menjelang pembebasan merasakan tekanan psikologis yang berpengaruh negatif terhadap psychological well-being. Penelitian ini bertujuan untuk mengetahui gambaran tingkat psychological well being warga binaan menjelang masa pembebasan. Metode penelitian deskriptif dengan pendekatan kuantitatif menggunakan alat ukur 42-item Ryff Psychological Well-Being Scale. Jumlah sampel 33 warga binaan menjelang bebas di Lembaga Pemasyarakatan Wanita Klas IIA Sukamiskin Bandung yang dipilih dengan metode non-random sampling melalui teknik accidental sampling. Analisis data berupa persentasi distribusi frekuensi. Hasil penelitian sebagian besar psychological well-being warga binaan menjelang pembebasan dalam kategori sedang. Skor dalam kategori tinggi paling banyak ditemukan pada dimensi hubungan positif dengan orang lain, sedangkan skor dalam kategori rendah paling banyak ditemukan pada dimensi penerimaan diri.Kata kunci: masa kebebasan, psychological well-being, warga binaan pemasyarakatan